1996
DOI: 10.1128/aem.62.1.266-268.1996
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Renewal Rate and Nutrient Concentration for the Production of the Marine Microalga Phaeodactylum tricornutum in Semicontinuous Cultures

Abstract: A factorial experiment comprising six nutrient concentrations and six renewal rates was set to optimize semicontinuous cultures of Phaeodactylum tricornutum. Maximal cell density, 85 ؋ 10 6 cells ml ؊1 , was obtained with 8 and 16 mmol of N per liter and a renewal rate of 10%. Protein stabilized at about 60% of the organic fraction for nitrogen-sufficient cultures. Both lipids and carbohydrates were stored as energetic reserves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The copyright holder for this preprint this version posted June 23, 2021. ; https://doi.org/10.1101/2021.06.23.449330 doi: bioRxiv preprint culture and they accumulate to a high cell density. Indeed, P. tricornutum reached abundances significantly higher than previously reported values, including under (semi-) continuous systems [60,61]. We believe this is the first demonstration that algae can accumulate to such high densities, purely driven by a novel cultivation technique.…”
Section: Discussionsupporting
confidence: 51%
“…The copyright holder for this preprint this version posted June 23, 2021. ; https://doi.org/10.1101/2021.06.23.449330 doi: bioRxiv preprint culture and they accumulate to a high cell density. Indeed, P. tricornutum reached abundances significantly higher than previously reported values, including under (semi-) continuous systems [60,61]. We believe this is the first demonstration that algae can accumulate to such high densities, purely driven by a novel cultivation technique.…”
Section: Discussionsupporting
confidence: 51%
“…Repeated batch cultivation has proved to be an excellent method for raising microbial productivity,24, 25 adjusting the nutrients feed rate to optimize the productivity26 and maintaining the microorganism at high growth rate 27. Some researchers adopted this method to enhance hydrogen production in dark fermentation 28, 29…”
Section: Resultsmentioning
confidence: 99%
“…semicontinuous cultivation shows that the specific growth rate of the microalga was increased when the medium renewal rate increased. The authors have also found that, with renewal rates of 40 to 50%, the percentage of conversion of nitrogen in the cells was below 100%, indicating that there was no nitrogen limitation [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…After a certain period of time, a portion of the culture medium with the microalgae is removed and replaced with fresh culture medium without cells [ 9 ]. This type of cultivation has operational advantages, such as dispensing with the constant changing of the inoculums and allowing the microorganism to grow at a high speed [ 10 ]. Although widely used, this system of cultivation has hardly been studied, and there is a lack of scientific work involving variables such as blend concentration and medium renewal rate.…”
Section: Introductionmentioning
confidence: 99%